ENVIRONMENTAL EDUCATION INSTITUTIONS AS A NEW TYPOLOGICAL OBJECT OF SUSTAINABLE ARCHITECTURE - Бармашина, Л.; Пивоваров, О.; Осипенко, O.; Кухарчук, П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The experience of many developed countries (Canada, Japan, Sweden and others) testifies to the need and opportunity to improve the environment based on the principles of environmental policy of each country. This requires a high level of environmental culture of the population and active public participation in nature conservation activities. Sustainable or sustainable development is a new principle of human cohabitation: the next generations must have the resources that are adequate to the existing ones. The concept of sustainable development emerged as a result of the integration of three main points of view: economic, social and environmental. Coordination of these approaches is a daunting task as the elements of sustainable or sustainable development must be balanced. A large group of sustainability issues is related to urban ecology. These include, first of all, the interaction of settlements with the environment. The main factor is the environmental safety of the living environment. Architectural ecology should study not only individual architectural objects, but also the architectural environment as a whole. This requires appropriate specialized areas, spaces and premises, that is, new architectural and urban development objects. Facilities such as complexes should include the landscaping of surrounding areas, open and covered landscaped areas, appropriately equipped special spaces, and educational buildings with classrooms, classrooms, laboratories, and the like. The new complex architectural and town-planning object (extracurricular institution of ecological education) should become part of the modern typology of buildings and structures. An example of a country where the concept of "environmental education" has acquired a much broader quality than obtaining a certificate or diploma is the United States. There is a so-called Odum School of Ecology at the University of Georgia. The mission of this school of ecology can be considered in particular the education of future generations of ecologists, cooperation with other departments of the university, promotion of environmental literacy of students and the public, interdisciplinary studies of the environment